Comparative pharmacodynamic and pharmacokinetic study of MIDD0301 and its (S) enantiomer. Issue 4 (4th March 2022) - Rashid Roni, M. S.; Zahn, Nicolas M.; Yocum, Gene T.; Webb, Daniel A.; Mian, Md Yeunus; Meyer, Michelle J.; Tylek, Anika S.; Cook, James M.; Emala, Charles W.; Stafford, Douglas C.; Arnold, Leggy A.
Abstract: MIDD0301 is being developed as an oral drug to relax airway smooth muscle (ASM) and reduce lung inflammation in asthma. We report a comparative study of MIDD0301 and its S isomer (MIDD0301S), and found that the compounds have equivalent affinity for γ‐aminobutyric acid type A receptor (GABAA R) expressed in rat brain, with half maximal inhibitory concentration values of 25.1 and 26.3 nM for the S and R enantiomers, respectively. Both compounds relaxed substance P contracted ASM within 30 min and neither enantiomer revealed affinity to 48 receptors in an off‐target screen. Both enantiomers reduced airway hyperresponsiveness (AHR) with nebulized and oral dosing in two mouse models of bronchoconstriction. In A/J mice, which are very sensitive to methacholine‐induced bronchoconstriction, we observed reduction of AHR at 10.8 mg/kg MIDD0301 and 15 mg/kg MIDD0301S. Using oral administration, 100 mg/kg/day for 3 days of either enantiomer was sufficient to reduce AHR. In a model of severe airway inflammation induced by interferon‐γ and lipopolysaccharide (LPS), we observed reduction of AHR at 7.2 mg/kg for both enantiomers using nebulized administration, and at 100 mg/kg for oral administration. MIDD0301 and MIDD0301S did not undergo Phase I metabolism. Glucuronidation was observed for both compounds, whereas only MIDD0301 formed the corresponding glucoside in the presence of kidney microsomes. Pharmacokinetic analysis identified glucuronides as the major metabolite with concentrations up to 20‐fold more than the parent compound. MIDD0301 glucuronide and MIDD0301 taurine bind GABAA Rs, although 10‐fold weaker than MIDD0301. In mouse blood, the taurine adduct was only observed for MIDD0301. Overall, both compounds exhibited similar receptor binding and pharmacodynamic properties with subtle differences in metabolism and greater oral availability and blood concentrations of MIDD0301S.